Արցախյան հարցի պատմության շուրջ (1918 թ.) - Հ. Բ. Աբրահամյան (ՀՀ ԳԱԱ հրատ.)
В истории Арцахского вопроса есть множество пробелов, являющихся следствием поверхностного анализа архивных материалов, противоречивости фактов. Исторические события, имевшие место в Арцахе в 1918 г., нуждаются в более доскональном исследовании и ряде уточнений. There are many gaps in the history of the Artsakh Issue that are the result of a superficial analysis of archival materials, contradictory facts. Historical events that took place in Artsakh in 1918 need more thorough research and a number of refinements.
Keywords: History; Modern History; D History